THE IMPACT ON INDIVIDUALS AND COMMUNITY HEALTH BY KITCHEN INSECTS AS BACTERIAL MECHANICAL VECTORS, TAIF, KSA - Sherifa Mostafa M. Sabra (Basrah Journal of Veterinary Research)
This paper was designed to evaluate the kitchen insects bacterial mechanical vectors (Cockroaches) and its impact on individual and community health in Taif, KSA, the mean incidence of bacterial loads turbidity were (3rd, 1st, 2nd, 4th and 5th group); (98.0, 97.2, 96.9, 96.5 and 96.2%) respectively, the mean was 96.96%. The mean incidence of bacterial growth evaluation were (+++ = heavy growth) in all groups, were in (3rd, 1st, 2nd, 4th and 5th group); (78.5, 77.2, 76.3, 76.1 and 76.0%) respectively, the mean revealed 76.82%. The mean incidence of bacterial Colony Forming Unit (CFU) / mL evaluation, the mean was (3.3 X 105) / mL, were (3.8, 3.5, 3.3, 3.1 and 2.9 X105) / mL, for (3rd, 1st, 2nd, 4th and 5th group) respectively. The mean incidence of bacterial Spp were isolated, which produced 12 bacterial Spp were (E. coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Proteus Spp and Citrobacter Spp) as (19.1, 16.2, 13.3, 12.2 and 8.3%) respectively, followed by bacteria (Shigella Spp, Staph. Spp, Strept. Spp, Serratia Spp, Bacillus Spp, Salmonella Spp and Campylobacter Spp) were (7.5, 6.4, 4.5, 4.2, 3.8, 2.4 and 2.1%) respectively. The conclusions confirmed the role of Cockroaches as a bacterial mechanical vector, which transferred and dropped of the pathogenic bacteria which caused food contamination, food poising and infectious diseases, that effected on the individuals and community health. So the insect control center (Insecticiders) must be arranged to eradicate the Cockroaches and also the kitchens hygiene must be improved to protect the individuals and community health.